On the 100th Anniversary of the Department of Electrometallurgy - Sukhyy , K.M.; Proidak , Yu.S. (Theory and Practice of Metallurgy, 2025)
The article reflects the origin and development of the electrometallurgical industry in Ukraine. The emphasis is placed on the role of the Department of Electrometallurgy at the Dnipro Metallurgical Institute in this process. The Department of Electrometallurgy was established in 1925. This was facilitated by the leading role of scientists, professors, doctors of technical sciences Telnyi S. I., Khytryk S. Y., Hasyk M. I., who made a significant contribution to the development of the electrometallurgical industry in Ukraine and the training of highly qualified specialists. In the article, the key stages of formation and development of electrometallurgy have been outlined, and the crucial role of scientists and teachers of the Department has been stated.